1994
DOI: 10.1111/j.1468-5957.1994.tb00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasoned Equity Offerings: The Case of All‐equity Firms

Abstract: Three theories have been widely proposed to explain the significant negative market response to the announcement of a new equity issue. By observing a similar negative effect in a sample of zero and near zero long‐term debt firms, we are able to conclude that the capital structure hypothesis is not the sole explanation. Regressions of announcement period abnormal returns against subsequent cashflow change while controlling for price pressure effects provide evidence in support of the information hypothesis. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Over the five-day event window, the share price on average drops a total of 3,8% following a rights issue announcement. This is consistent with the findings of international and local research (White and Lusztig, 1980;Asquith and Mullins, 1986;Mikkelson and Partch, 1986;Smith, 1986;Dierkens, 1991;Pilotte, 1992;Youds, Firer and Ward, 1993;Bayless, 1994;Sant and Ferris 1994;Bohren et al, 1997;Bhana, 1998 andHorne, 1999).…”
Section: Interpretation Of Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Over the five-day event window, the share price on average drops a total of 3,8% following a rights issue announcement. This is consistent with the findings of international and local research (White and Lusztig, 1980;Asquith and Mullins, 1986;Mikkelson and Partch, 1986;Smith, 1986;Dierkens, 1991;Pilotte, 1992;Youds, Firer and Ward, 1993;Bayless, 1994;Sant and Ferris 1994;Bohren et al, 1997;Bhana, 1998 andHorne, 1999).…”
Section: Interpretation Of Resultssupporting
confidence: 89%
“…International and local researchers have all found that there is a significant negative share price response to the announcement of a rights issue (White and Lusztig, 1980;Asquith and Mullins, 1986;Mikkelson and Partch, 1986;Smith, 1986;Dierkens, 1991;Pilotte, 1992;Youds, Firer and Ward, 1993;Bayless, 1994;Sant and Ferris 1994;Bohren, Eckbo and Michalsen, 1997;Bhana, 1998 andHorne, 1999).…”
Section: The Influence Of Economic Factors On Rights Issue Announcemementioning
confidence: 99%
“…5 Prior studies that examine interest on borrowing include Berger and Udell (1995) and Petersen and Rajan (1994) but these studies do not focus on all-equity firms or investment opportunities. 6 Prior studies that examine all-equity firms include Agrawal and Nagarajan (1990), Gardner and Trzcinka (1992), Sant and Ferris (1994) and Iyengar et al (2005). 7 If debt holders are very risk-averse, they will refrain from lending activities.…”
Section: Hypothesesmentioning
confidence: 99%
“…as a positive signal) or purchases followed immediately by sales as a 'sell' (or negative signal), with all other patterns treated as neutral. Cogent arguments can be made for most of the commonly adopted treatments (see Sant and Ferris, 1994 where option exercises are claimed to represent a positive signal to the market). 14 John and Lang (1991) analyse the effect of trading which takes place three, six, nine and twelve months before dividend-initiation announcements, but report that lengthening the period adds nothing to the explanation of subsequent abnormal returns.…”
Section: Classification Of the Signalmentioning
confidence: 99%